ANALISIS EFISIENSI PRODUKSI USAHATANI KELAPA DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Pasaribu, Agustina; Bakce, Djaimi; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Keritang subdistrict has a wide enough area of coconut farming, but it’s production is susceptible to fluctuations that tends to decrease and it’s productivity is low. This coconut farming still not use the right cultivation techniques. This can be seen from the behavior of farmers. Most of them do not use fertilizer, pesticides, and the farmer did not make the plants maintenance with good. This study aims to determine the efficiency of production activity of coconut farming  in Keritang subdistrict, Indragiri Hilir Municipality. Methods of analysis is Data Envelopment Analysis (DEA), it is non parametrik methods based on linear programming. Based on the results of the efficiency of production showed that most of the coconut farming is inefficient technically, namely the use of labour has been more than capacity should be. Most coconut’s farmers also inefficient in allocation, because the price of inputs that paid by farmers greater than the output that they have received. If this coconut farming is inefficient in technical and it’s allocation, then the coconut farming also inefficient in the economy. According to these findings in economic, then (1) need any help from the government and the participation of farmers to bring out coconut farming  being appropriate with the right technique of coconut culvitation (2) efforts of the government is needed to control the input price and increase the output price (3) government intervention in terms to eliminate practice of monopsonic.     Key words : Coconut Farming, The efficiency of productions